The structure and performance of Ethiopia's financial sector in the pre- and post-reform period with a special focus on banking - Alemayehu Geda (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
Since 1992 Ethiopia has been engaged in liberalizing its financial sector. The hallmark of the strategy is gradualism. The approach is not without problems especially from Bretton Woods Institutions that saw the reform as a sluggish process. This study examines this liberalization program by analyzing the performance of the sector before and after the reform. The study notes that given the nascent development of the financial sector in the country, the relatively good shape in which the existing financial institutions find themselves, and given that supervision and regulation capacity of the regulating agency is weak, the government's strategy of gradualism and its over all reform direction is encouraging. However, we argue for charting out clearly defined time frame for liberalization and exploring the possibility of engaging with foreign banks to acquire new technology that enhance the efficiency of the financial sector in general and the banking sector in particular.
Keywords: G20; G21; G32; O16; 330; financial sector development; growth; banking; financial liberalization; Ethiopia; Africa; Bank; Finanzsektor; Äthiopien